2010
DOI: 10.1111/j.1469-185x.2010.00171.x
|View full text |Cite
|
Sign up to set email alerts
|

Measuring biodiversity to explain community assembly: a unified approach

Abstract: One of the oldest challenges in ecology is to understand the processes that underpin the composition of communities. Historically, an obvious way in which to describe community compositions has been diversity in terms of the number and abundances of species. However, the failure to reject contradictory models has led to communities now being characterized by trait and phylogenetic diversities. Our objective here is to demonstrate how species, trait and phylogenetic diversity can be combined together from large… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
605
4
10

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 551 publications
(628 citation statements)
references
References 134 publications
(192 reference statements)
9
605
4
10
Order By: Relevance
“…In central Chile, small‐sized barnacles that share similar environmental tolerances in the high intertidal show no evidence for competitive advantages of one species over the other, suggesting that ecological equivalence can be common at this height of the shore (Shinen & Navarrete, 2010, 2014)—complementarity in other traits, such as filtration rates (e.g., Valdivia et al., 2009), should be further analyzed to assess niche partitioning in this model system. At the low‐intertidal fringe, we observed that SESFRic was greater than expected at random, indicating the occurrence of species with dissimilar functional traits and an expanded coverage of the trait space (Pavoine & Bonsall, 2011). Predation of dominant competitors such as medium‐sized mussels by shallow subtidal seastars and muricid gastropods could facilitate the establishment of subordinate species (Moreno, 2001; Navarrete & Castilla, 2003; Paine, 1966) with different traits and thus increase functional divergence.…”
Section: Discussionmentioning
confidence: 74%
“…In central Chile, small‐sized barnacles that share similar environmental tolerances in the high intertidal show no evidence for competitive advantages of one species over the other, suggesting that ecological equivalence can be common at this height of the shore (Shinen & Navarrete, 2010, 2014)—complementarity in other traits, such as filtration rates (e.g., Valdivia et al., 2009), should be further analyzed to assess niche partitioning in this model system. At the low‐intertidal fringe, we observed that SESFRic was greater than expected at random, indicating the occurrence of species with dissimilar functional traits and an expanded coverage of the trait space (Pavoine & Bonsall, 2011). Predation of dominant competitors such as medium‐sized mussels by shallow subtidal seastars and muricid gastropods could facilitate the establishment of subordinate species (Moreno, 2001; Navarrete & Castilla, 2003; Paine, 1966) with different traits and thus increase functional divergence.…”
Section: Discussionmentioning
confidence: 74%
“…These indices showed that functional diversity was comparatively rich in Acanthopanax senticosus communities compared to that in other forests in this area [1,13]. The variability of functional diversity was dependent on the variation of environmental variables [12,17]. Fuzzy index and SOFM index were significantly correlated with elevation and slope (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…Implement conservation actions 6. Maintain the required values of conservation areas Numerous indices have been developed to measure the originality of species ( Vane-Wright et al 1991;Pavoine et al 2005a;Isaac et al 2007), or phylogenetic diversity (Faith 1992;Schweiger et al 2008;Pavoine and Bonsall 2011;Faith chap-ter "The PD Phylogenetic Diversity Framework: Linking Evolutionary History to Feature Diversity for BiodiversityConservation"). The former measures assign a value for each species based on their dissimilarity from other species, whereas the latter look at an assemblage of species as a whole.…”
Section: Boxmentioning
confidence: 99%